A cross–nation comparative study of mobile learning. (2nd September 2014) - Zhang, Lihong; Yang, Jiaqin; Wei, June
This paper describes a comparative study investigating the effectiveness and influence of college students on mobile learning behaviour between USA and China. The result of this study reveals that among the three aspects of mobile learning, cognitive load, satisfaction and achievement, there exists a statistically significant difference between China and US college students, and the related influencing factors have demonstrated a meaningful and significant impact. Based on the results of this study, managerial insights and practical implications for marketing strategies in the mobile learning market are discussed and recommended along with the future research direction.